ANALGESIC ACTIVITY OF TRANSDERMAL PATCH ETHANOL EXTRACT PIPER NIGRUM L FRUCTUS WITH SOME ENHANCERS ON MICE - Lucia Hendriati; Iwan Sahrial Hamid; Teguh Widodo; Regiskha Hermandanie Surya; Alif Ekacahya Wahyudi; Dwi Damayanti Rasdianto (Universitas Muhammadiyah Magelang, 2021)
Piper nigrum L fructus with active compound piperin had been known have an analgesic effect. Ethanol extract of Piper nigrum formulated to transdermal patch to reduce side effect of analgesic oral. The aim of this research was to know the effect of sodium lauryl sulphate, Tween 80, isopropyl myristate as enhancer of transdermal patch ethanolic extract of Piper nigrum L. Analgesic effect of Piper nigrum L. carried out by writhing method after acetic acid induction in mice. Parameters used were the number of writhing and macrophage from peritoneal fluid of mice at the end of this study. Based on this study, ethanol extract of Piper nigrum had an analgesic effect. The used of sodium lauryl sulphate 5%, Tween 80 5%, isopropyl myristate6% as enhancer increased the analgesic effect of Piper nigrum L.